Genome Duplication: The Heartbeat of Developing Organisms - DePamphilis, Melvin L. (Curr Top Dev Biol, 2016)
The mechanism that duplicates the nuclear genome during the trillions of cell divisions required to develop from zygote to adult is the same throughout the eukarya, but the mechanisms that determine where, when and how much nuclear genome duplication occur regulate development and differ among the eukarya. They allow organisms to change the rate of cell proliferation during development, to activate zygotic gene expression independently of DNA replication, and to restrict nuclear DNA replication to once per cell division. They allow specialized cells to exit their mitotic cell cycle and differentiate into polyploid cells, and in some cases, to amplify the number of copies of specific genes. It is genome duplication that drives evolution, by virtue of the errors that inevitably occur when the same process is repeated trillions of times. It is, unfortunately, the same errors that produce age-related genetic disorders such as cancer.